Coherent diffractive imaging via a rotatable cylindrical lens. (January 2020) - Zheng, Shuiqin; Shangguan, Huangcheng; Zeng, Xuanke; Li, Ying; Lu, Xiaowei; Xu, Shixiang; Fan, Dianyuan
Highlights: Proposing an imaging technique called rotary astigmatic diffractive imaging. Simple setup and easy calibration. Convergence of the setup increases with the number of constraint patterns. The uniqueness of the recovery phase can be guaranteed. Abstract: This paper proposed a diffractive imaging technology called rotary astigmatic diffractive imaging (RADI). The system uses a rotatable cylindrical lens for rotary astigmatic modulation and a camera for collecting the diffractive patterns distorted in different angles. Then a field can be reconstructed with the patterns by an iterative algorithm. Compared with the original astigmatic diffractive imaging system, our simulations show RADI system has the greater performance of convergence with the same number of constrained patterns. In addition, it is easy for RADI to increase the number of diffraction measurements to accelerate the convergence further. Considering the center of the cylindrical lens does not coincide with the center of rotation, a calibration method is proposed. An optical vortex of charge two is reconstructed experimentally demonstrating the system can solve the problem of unique phase recovery. Besides, the reconstructions of a USAF resolution chart with different numbers of constrained patterns shows the rate of convergence increases obviously with the increase of the number of diffraction measurements. The reconstruction shows the resolution of our system is about 14.25 lp/mm, which is 60% of the diffraction limited resolution. Our RADI can provide a high-performance way but with simple setup to realize field reconstruction.